Static and dynamic evaluations for large square solar sail concept based on scalable prototype validation. (June 2019) - Yang, Chen; Zheng, Wanzheng; Zhang, Xuepan; Wang, Li; Hou, Xinbin
Abstract: This study aims to propose a static and dynamic evaluation for 160 m solar sail by comparing the results obtained using an 8 m scalable principle prototype. Based on the model updating and parameter modification theories, the finite element analysis (FEA) model of the 8 m prototype is constructed, and results are obtained to validate the effectiveness of the proposed numerical simulation method. The static deformation is compared with experimental data with errors in acceptable limits. Moreover, the numerical simulation and analysis method for wrinkle patterns are also applied based on the structural buckling theory and linear combination technology. The calculated indices of peak-valley value, half-wavelength, and wrinkle number are compared with the prototype experiment. By validating the numerical simulation approach in the 8 m prototype, the same analysis method can be directly extended in the application of the 160 m solar sail. The deformation response of the overall system and wrinkle patterns of the 160 m sail are provided. The transient dynamic responses of acceleration, displacement, and vibration amplitudes are also simulated and compared using different parameters. All the results obtained herein provide valuable suggestions and reference to large solar sail design in the future. Highlights: The simulation and analysis method for solar sail is validated by scalable prototype. Wrinkles of sail are simulated based on buckling theory and validated by experiment. Static deformation, stress and wrinkles are analyzed to evaluate 160 m sail concept. Transient dynamic responses of 160 m sail with different parameters are provided.